2017
DOI: 10.1038/srep41154
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the allosteric regulation of artificial muscarinic and dopaminergic ligand-gated potassium channels by protein engineering of G protein-coupled receptors

Abstract: Ligand-gated ion channels enable intercellular transmission of action potential through synapses by transducing biochemical messengers into electrical signal. We designed artificial ligand-gated ion channels by coupling G protein-coupled receptors to the Kir6.2 potassium channel. These artificial channels called ion channel-coupled receptors offer complementary properties to natural channels by extending the repertoire of ligands to those recognized by the fused receptors, by generating more sustained signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…When the same approach of incremental deletions was previously used between M2=K0-25 and M2=K-9-25, a linear correlation between the length of the M2 C-ter and the regulation of the channel was observed [3]. In Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…When the same approach of incremental deletions was previously used between M2=K0-25 and M2=K-9-25, a linear correlation between the length of the M2 C-ter and the regulation of the channel was observed [3]. In Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, for example, the human M2 muscarinic receptor opens the ion channel upon acetylcholine (ACh) binding, while D2 L (D2) dopaminergic receptor closes it in the presence of dopamine. In a previous study [3], we demonstrated that the length of the receptor C-termini controls the sign and the amplitude of the channel regulation. In the muscarinic ICCR, the receptor C-ter was shortened by 9 residues in order to mimic the D2 C-ter length, resulting in an inversion of the channel regulation leading to an inhibition of the channel by ACh (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations